Characterization of a Prophage-Free Derivative Strain of Lactococcus lactis ssp. lactis IL1403 Reveals the Importance of Prophages for Phenotypic Plasticity of the Host - Aucouturier, Anne; Chain, Florian; Langella, Philippe; Bidnenko, Elena (Frontiers in Microbiology, 2018)
Increasing number of sequenced genomes of Lactococcus lactis, a model lactic acid bacterium largely used in dairy industry and in the domain of human health, provided an evidence for constant association of lactococcal genomes with prophages and prophage-like elements. The prophage-related sequences encompass up to 10% of the chromosomes and thus contribute significantly to the genetic diversity of lactococci. However, the impact of resident prophages on L. lactis physiology is presently unknown. Genome of the first sequenced prototype strain L. lactis subsp. lactis IL1403 contains six prophages-like elements representing in total 6.7% of the IL1403 chromosome. Diverse prophage genes other than encoding phage repressors have been shown to be expressed in lysogenic conditions, suggesting that prophage-borne genes can modulate physiology of their host. To elucidate the role of resident prophages in the relation to L. lactis behavior in different growth conditions, we constructed and characterized a first prophage-free IL1403 derivative strain. This strain provides unique experimental opportunities for studying the different aspects of lactococcal physiology in the well defined genetic background. Here we show that resident prophages considerably modify growth and survival of host strain in different conditions including gastrointestinal environment, they also impact cellular autolytic properties, susceptibility to virulent bacteriophages and antimicrobial agents. Therefore, individual prophages contribute significantly to the lactococcal cells’ physiology and thus might play an important role in the adaptation of L. lactis to cultivation and environmental conditions.